PENGGUNAAN METODE UN-IGME UNTUK MENGESTIMASI KEMATIAN BAYI DAN BALITA DI PERKOTAAN DAN PERDESAAN DI INDONESIA - Maretalinia Maretalinia; Suyitno Suyitno; Dyah Suryani (SPIRAKEL, 2021)
The estimation of child mortality is very important, especially for the countries with low quality of death registration. The child mortality (IMR (Infant Mortality Rate) and U5MR (Under Five Mortality Rate) will be important to plan, organize, and evaluate the development programs. This study aimed to estimate the child mortality (IMR and U5MR) in urban and rural area of Indonesia. The indirect estimation method with one census period data was used to estimate the child mortality by using the data of: children ever born, children still alive, and number of women in reproductive age. The child mortality declined from 1997 to 2006 in urban and rural area but the child mortality in rural area was higher compared to urban area. The quality of death registration in Indonesia remains low and need to be improved. The estimation of IMR and U5MR in urban were 18 and 27 per 1000 mortality, respectively. On the other hand, the estimation of IMR and U5MR in rural were 24 and 36 per 1000 mortality, respectively. The high gap of characteristics between urban and rural area need to be explored to prevent the increasing number of IMR and U5MR.